Villages of Porabje: Individual elements of the Hungarian settlement network - Balogh, András (Journal for Geography, 2016)
Special feature of Porabje settlements can be detected on some geographical aspects within the national settlement network. Unique features of these settlements even these features are not exclusive in themselves regarding all the administratively independent settlements form such a specific region of Hungary on the base of that the following can be stated. The Vend-region occupies prominent place among the regions of Hungary. These special features are studied in this study on the base of the following aspects: spatial location, history, ethnic composition, ethnographic aspects, small village and sporadic settlement characteristic and development possibilities. However Szentgotthárd (Monošter) played important role in life of the Slovenians in Hungary too the essay focuses on the analysis of the settlements in the Porabje region.
Keywords: Porabje; Slovenians in Hungary; ethnographical region; small villages; sporadic settlements; development possibilities